The effects of gluteal stretching vs. Lightback® on hip rotation range of motion and posterior chain flexibility in healthy subjects: a cross-over clinical trial - Charles Cotteret; Jaime Almazán-Polo; Fabien Guérineau; Ángel González de-la-Flor (PeerJ)
Introduction Hip range of motion (ROM) across various planes is necessary in sport-related activities. Static stretching was commonly used to improve hip ROM. The Lightback system, a novel compression device, has been developed to enhance hip mobility by applying controlled axial forces on the femur. This study aimed to evaluate the effectiveness of the Lightback system in improving hip ROM and posterior chain flexibility compared to conventional static stretching. Methods A randomized cross-over trial was carried out in 31 physically active participants (62 lower limbs; n = 31 Lightback group (LBG) and n = 31 stretching group (SG)). Hip rotation at two positions of hip flexion (active and passive external (ER) and internal rotation (IR) at 0–90° hip flexion), total rotation ROM (TRROM), and the flexibility of the posterior chain (active knee extension test (AKE) and active straight leg raise (ASLR)) were measured before and after the stretching session. Results LBG demonstrated significantly greater improvements in hip ER and IR compared to the SG. Specifically, the LBG showed significant increases in active ER at 0° (p = 0.002) and 90° (p < 0.001) of hip flexion, as well as IR at 0° (p = 0.007) and 90° (p < 0.001). TRROM in neutral and at 90° of hip flexion also improved significantly in the LBG (p < 0.001). In passive ROM, the LBG exhibited significant increases in ER at 0° (p < 0.001), IR at 90° (p = 0.001), and TRROM at both positions (p < 0.001), compared to the SG. Regarding posterior chain flexibility, both groups improved in AKE and ASLR (p < 0.001), but the LBG showed a significantly larger effect in ASLR (p < 0.001), with no significant difference between groups in AKE. Conclusion This study demonstrated that both the Lightback system and static gluteal stretching improved passive hip ROM. However, the Lightback system showed greater improvements in active ROM, particularly in external and internal rotation at various degrees of hip flexion, as well as in posterior chain flexibility. Notably, the Lightback system significantly enhanced large improvement in the ASLR test.